Chronic Granulomatous Disease First Diagnosed in Adulthood Presenting With Spinal Cord Infection - Schwenkenbecher, Philipp; Neyazi, Alexandra; Donnerstag, Frank; Ringshausen, Felix C.; Jacobs, Roland; Stoll, Matthias; Kirschner, Philip; Länger, Florian Peter; Valizada, Emil; Gingele, Stefan; Wegner, Florian; Sühs, Kurt-Wolfram; et al. (Frontiers in Immunology, 2018)
Chronic granulomatous disease (CGD) is a rare genetic immunodeficiency which is characterized by recurrent severe bacterial and fungal infections caused by a defect in phagocytic cells due to loss of superoxide production. The disease usually manifests within the first years of life. Early diagnosis allows therapeutic intervention to improve the limited life expectancy. Nevertheless, only half of the patients exceed the age of 25. Here, we present the case of a 41-year old female patient who presented with an extensive spinal cord infection and atypical pneumonia mimicking tuberculosis. The medical history with recurrent granulomatous infections and microbiological findings with multiple unusual opportunistic pathogens was the key to the diagnosis of chronic granulomatous disease which is exceptionally rare first diagnosed in patients in the fifth decade of life. The late diagnosis in this case was likely to the lack of knowledge of the disease by the treating teams before but not because the patient did not have typical CDG infections along her life. The extensive progressive developing granulomas in our patient with fatal outcome raise the question of early immunosuppressive therapy in addition to anti-infectious treatment. We recommend appropriate CGD diagnostics in adult patients with unclear granulomatous diseases of the nervous system.